Exercise training impacts skeletal muscle remodelling induced by metabolic syndrome in ZSF1 rats through metabolism regulation - Nogueira-Ferreira, Rita (2023)
Metabolic syndrome (MetS), characterized by a set of conditions that include obesity, hypertension, and dyslipidemia, is associated with increased cardiovascular risk. Exercise training (EX) has been reported to improve MetS management, although the underlying metabolic adaptations that drive its benefits remain poorly understood. This work aims to characterize the molecular changes induced by EX in skeletal muscle in MetS, focusing on gastrocnemius metabolic remodelling. 1H NMR metabolomics and molecular assays were employed to assess the metabolic profile of skeletal muscle tissue from lean male ZSF1 rats (CTL), obese sedentary male ZSF1 rats (MetS-SED), and obese male ZF1 rats submitted to 4 weeks of treadmill EX (5 days/week, 60 min/day, 15 m/min) (MetS-EX). EX did not counteract the significant increase of body weight and circulating lipid profile, but had an anti-inflammatory effect and improved exercise capacity. The decreased gastrocnemius mass observed in MetS was paralleled with glycogen degradation into small glucose oligosaccharides, with the release of glucose-1-phosphate, and an increase in glucose-6-phosphate and glucose levels. Moreover, sedentary MetS animals' muscle exhibited lower AMPK expression levels and higher amino acids' metabolism such as glutamine and glutamate, compared to lean animals. In contrast, the EX group showed changes suggesting an increase in fatty acid oxidation and oxidative phosphorylation. Additionally, EX mitigated MetS-induced fiber atrophy and fibrosis in the gastrocnemius muscle. EX had a positive effect on gastrocnemius metabolism by enhancing oxidative metabolism and, consequently, reducing susceptibility to fatigue. These findings reinforce the importance of prescribing EX programs to patients with MetS.